IN SILICO STUDY ON PREDICTING EFFECTS OF H243L MUTATION IN BACILLUS SUBTILIS LEVANSUCRASE TOWARDS SUCROSE BINDING AFFINITY - Andrew Sudijanto, Jason
Levan is a branched polysaccharide made from fructose monomers linked by ?(2-6) glycosidic bond and ?(2-1) glycosidic bond. Currently, levan has many applications in some industries including food, cosmetic, and food industires. In vivo levan is synthesized with the help of levansucrase (EC 2.4.1.10, LS) using sucrose as its substrate. Levan produced by this biosynthesis process varies in size depending on the species of levansucrase. Some levansurcase can synthesize high molecular weight levan and some can only synthesize low molecular weight levan or fructooligosaccharides. This difference is hypothesized to be related to which amino acids are involved in substrate binding. This study will analyze structure and function of levansucrase using in silico approach to determine which amino acids contributes to LS substrate binding affinity. Previous study suggested that His-243 residue in Bacillus subtilis levansucrase has an important role in substrate binding affinity. The same study showed that mutating this residue into a Leu increases affinity toward substrate resulting in higher molecular weight levan synthesized. In this study the effect of this mutation is predicted using in silico methods, including molecular docking with Autodock VINA, molecular dynamics simulation (MD) with Gromacs 2018. Gromacs MD trajectories are used for binding free energy calculation using gmx_MMPBSA program. Molecular docking was done by attaching sucrose molecule into crystal structure of wild-type (WT) Bacillus subtilis LS obtained from protein databank (PDB code 1OYG). LS with His243 mutated to Leu will also receive the same treatment with molecular docking and MD. Docking results analyzed using Ligplot+ showed that residue number 243 doesn’t interact directly with sucorse. H243L mutation free energy calculation using FEP gives the value of ?Gmutation = +6,797 kkal/mol, which is not thermodinamically favorable. MD results suggested that the effect of H243L mutation on protein structure is non-local. MM-PBSA calculation at the end of the LS-sucrose complex simulation showed that H243L mutation improves LS sucrose binding affinity from ?Gbind WT-sucrose = ?5,488 kkal/mol to ?Gbind H243L-sucrose = ?10,377 kcal/mol. After further investigation it is suggested that H243L mutation enhances the ability of nearby residues like Glu340 and Arg246 to form hydrogen bonds with substrate.